The regulatory mechanism of p38/MAPK in the chondrogenic differentiation from bone marrow mesenchymal stem cells - Ma, Ning (J Orthop Surg Res, 2019)
BACKGROUND: Osteoarthritis (OA) is a degenerative joint disease characterized by articular cartilage degradation and joint inflammation, in which growth factors are significantly involved. The extracellular signal-regulated p38 MAPK pathways play important roles in the regulation of osteogenic and chondrogenic differentiation in bone marrow mesenchymal stem cells (BMSCs). However, the exact mechanism remains unclear. METHODS: In this study, the chondrogenic differentiation of human BMSCs was initiated in micromass culture in the presence of TGF-β1 for 14 days. Quantitative RT-PCR and Western blot were performed to detect the transfection effect of shRNA-p38 interfering plasmid in BMSCs. The protein expressions of p/t-p38, SOX9, collagen II, Aggrecan, p/t-Smad1, and p/t-Smad4, as well as the kinase activities of p38/ERK/JNK pathway, were investigated using Western blot analysis. Additionally, the level of chondroitin sulfate and glycosaminoglycans (GAG) expression were measured by Alcian blue staining and GAG assay kit via qualitative and quantitative methods, respectively. RESULTS: The results demonstrated that p38 pathway was activated in the chondrogenic differentiation of BMSCs induced by TGF-β1. Cartilage-specific genes and chondrogenic regulators, such as SOX9, collagen II, Aggrecan, and GAG, were upregulated by TGF-β1, which could be reversed by predisposed with shRNA-p38 interfering plasmid and p38-MAPK inhibitors (SB203580). Moreover, the activation of p38/ERK/JNK pathways in the presence of TGF-β1 was suppressed by shRNA-p38 and SB203580 treatment. CONCLUSION: Collectively, the activation of p38/ERK/JNK/Smad pathways plays a facilitated role in the chondrogenic differentiation induced by TGF-β1. After suppressing the p38 pathway, the chondrogenesis can be inhibited, which can be used to guide the treatment of osteoarthritis.